Histological analyses of thermal effect caused by 1.2 W diode laser irradiation at rat periodontal pockets - Fontana, C. R.; Kurachi, C.; Marcantonio, Rosemary Adriana Chierici [UNESP]; Costa, Carlos Alberto de Souza [UNESP]; Bagnato, V. S. (Maik Nauka/interperiodica/springer, 2009)
The aim of this in vivo study was to evaluate the thermal effects caused by 810 nm 1.2 W diode laser irradiation of periodontal tissues. Despite all data available concerning the laser application for periodontal treatment, one of the most relevant challenges is to prevent the harmful tissue heating induced by different clinical protocols. Periodontal pockets were induced at molars in 96 rats. Several irradiation powers under CW mode were investigated: 0, 400, 600, 800, 1000, 1200 mW. The pockets were irradiated using a 300 A mu m frontal illumination fiber. The animals were killed at 4 or 10 days after irradiation. The mandible was surgically removed and histologically processed. The histological sections stained with H/E demonstrated that irradiation parameters up to 1000 mW were thermally safe for the periodontal tissues. The sections stained with Brown & Brenn technique evidenced bacteria in the periodontal tissues. Consequently, the diode laser irradiation as a unique treatment was not capable to eliminate bacteria of the biofilm present in the pockets. According to the methodology used here, it was concluded that the thermal variation promoted by a diode laser can cause damage to periodontal tissues depending on the energy density used. The 1.2 W diode laser irradiation itself does not control the bacteria present in the biofilm of the periodontal pockets without mechanical action. The knowledge of proper high intensity laser parameters and methods of irradiation for periodontal protocols may prevent any undesirable thermal damage to the tissues.